Additive Analgesic Effect of Transcranial Direct Current Stimulation Together with Mirror Therapy for the Treatment of Phantom Pain. Issue 2 (29th November 2020) - Segal, Nitza; Pud, Dorit; Amir, Hagai; Ratmansky, Motti; Kuperman, Pora; Honigman,, Liat; Treister,, Roi
Abstract: Objective: Current analgesic treatments for phantom pain are not optimal. One well-accepted yet limited nonpharmacological option is mirror therapy, which is thought to counterbalance abnormal plasticity. Transcranial direct current stimulation (tDCS) is an emerging approach believed to affect the membrane potential and activity threshold of cortical neurons. tDCS analgesic effectiveness, however, is mild and short, rendering it a noneffective stand-alone treatment. This study aimed to assess if a combination of mirror therapy with tDCS results in a superior analgesic effect as compared with mirror therapy alone in patients suffering from phantom pain due to recent amputation. Design: Following ethical approval, eligible patients provided informed consent and were randomly assigned to a study treatment group that continued for 2 weeks (once daily): 1) mirror therapy; 2) mirror therapy and sham tDCS; or 3) mirror therapy and tDCS. Assessments were done before treatment; at the end of treatment weeks 1 and 2; and at 1 week, 1 month, and 3 months following treatment. The primary outcome measure was pain intensity. Secondary measures were derived from the Short Form McGill Pain Questionnaire and the Brief Pain Inventory. Results: Thirty patients were recruited, and 29 patients completed the study. Three months following treatment, pain intensity was significantly ( P <0.001) reduced in the combined treatment group (reduction of 5.4±3.3 points) compared with the other study arms (mirror therapy, 1.2±1.1; mirror therapy and sham tDCS, 2.7±3.2). All secondary outcome results were in line with these findings. Conclusions: Combining tDCS with mirror therapy results in a robust long-lasting analgesic effect. These encouraging findings may contribute to the understanding of the underlying mechanisms of phantom pain.